Bullous pemphigoid induced by metamizole in a pediatric patient - Isa An; Derya Ucmak; Ibrahim Ibiloglu (Wolters Kluwer Medknow Publications, 2018)
Bullous pemphigoid (BP) is an autoimmune bullous disease commonly seen in adult population but rarely encountered in the pediatric population. Although the exact etiology of BP remains unclear, various vaccines, infectious agents, and drug use have been blamed in the etiology of BP. Here, we present a 14-year-old patient who developed BP after using metamizole and whose diagnosis was clinically and histopathologically confirmed.